Perspectives on When to Schedule the EM Clerkship and Its Effect on Students in an Environment of Changing Curricula - Matthew Van Ligten; Drew Barron Kraus; Douglas Rappaport; Lauren Querin; Wayne A Martini (Journal of Medical Education and Curricular Development)
Purpose This study investigates medical students’ opinions on the optimal timing for taking the emergency medicine (EM) clerkship and its effects on preparedness for subsequent clerkships and the USMLE (United States Medical Licensing Examination) Step 2 examination. Methods A cross-sectional survey was conducted among third- and fourth-year students at the Mayo Clinic Alix School of Medicine. The survey collected opinions on the optimal timing for the EM clerkship and its impact on self-efficacy as well as perceived preparedness for future clerkships and the USMLE Step 2 examination. Results Only 5% of third-year EM clerkship students felt they would have been more prepared in their fourth year. Conversely, 70% of fourth-year students believed they were more prepared than if they had taken it in their third year. Students were evenly split on if an earlier EM clerkship would have been helpful for subsequent clerkships. 88% of pre-USMLE Step 2 students found it helpful for Step 2, while 37% of post-USMLE Step 2 students felt it would have helped their preparedness. Additionally, 96% of students stated the EM clerkship increased their confidence in seeing patients. 43% of those who took the clerkship in their fourth year reported they would have considered EM as a specialty had they taken it earlier. Most students recommended taking the EM clerkship during the second 6 months of clerkships. Conclusion There are mixed opinions among medical students regarding the helpfulness of taking the EM clerkship earlier for subsequent clerkships and USMLE Step 2 preparedness. However, the majority recommend taking the EM clerkship earlier. A significant proportion of participants would have considered EM as a specialty if they had taken the clerkship earlier. Furthermore, 96% reported increased self-efficacy. Therefore, encouraging students to take the EM clerkship earlier may increase self-confidence and allow for earlier career exploration.